1
$\begingroup$

Let $A$ be a matrix with determinant 1. Then we call a general affine transformation, a transformation of the form \begin{align*} \begin{bmatrix}x'\\y'\end{bmatrix}=A\begin{bmatrix}x\\y\end{bmatrix}+\begin{bmatrix}r\\s\end{bmatrix} \end{align*} Let $p_1,p_2,p_3$ be colinear points. Prove that \begin{align*} \frac{||p_2-p_1||}{||p_2-p_3||} \end{align*} Is preserved under these transformations.

I have been working this proof for some time now. I can break these transformations down into pure translations, rotations, and scalings. Everything works out quite nicely for the translations and the rotations but if I try to prove this using a scaling matrix i.e. a matrix of the form \begin{align*} \begin{bmatrix}a&0\\0&1/a\end{bmatrix} \end{align*}.

Any help is greatly appreciated.

$\endgroup$
  • $\begingroup$ Use \| instead of || for the vector norm. $\endgroup$ – amd Feb 26 at 23:57
  • $\begingroup$ This “general” affine transformation isn’t as general as it could be. We only need $\det A\ne0$. With $\det A=1$, the transformation also preserves areas and orientation. $\endgroup$ – amd Feb 26 at 23:59
0
$\begingroup$

Since $p_1, p_2$ and $p_3$ are colinear, we can write $\vec{v} = p_2 - p_3$ and $p2 - p_1 = \lambda \vec{v}$ whence $$ \frac{||p_2-p_1||}{||p_2-p_3||} = \lambda $$ Now write the components of $v$ as $(v_x, v_y)$; we have $$ ||p_2-p_3|| = (v_x, v_y) \\ ||p_2-p_1|| = (\lambda v_x, \lambda v_y) $$

Now apply (multiply by) a scaling transformation. Although it is adequate to just use your example, it might be illuminating to use a general matrix $$S = \pmatrix{a & b \\ c & d}$$with $ad-bc = 1$. $$ S (p_2-p_3)= \pmatrix{ a \,v_x + b \,v_y \\ c \,v_x + d \,v_y}\\ S (p_2-p_1) = \pmatrix{ a \lambda \,v_x + b \lambda\,v_y \\ c \lambda\,v_x + d \lambda \,v_y} = \lambda S(p2-p3)\\ $$

$\endgroup$
0
$\begingroup$

You don’t really need to break the transformation down into cases. This is a straightforward consequence of the linearity of $A$ and homogeneity of norms.

Note first that the translation part of the transformation—the addition of $[r,s]^T$—is irrelevant since it cancels when you subtract the images of the points from each other.

The line through $p_2$ and $p_3$ can be parameterized as $(1-\lambda)p_2+\lambda p_3$. Since $p_1$ is colinear with these two points, there’s some real $\lambda$ for which $p_1 = (1-\lambda)p_2+\lambda p_3$, from which $$p_2-p_1 = p_2-((1-\lambda)p_2+\lambda p_3) = \lambda(p_2-p_3)$$ and so $${\|p_2-p_1\|\over\|p_2-p_3\|} = |\lambda|.$$

Now, by linearity, $Ap_1 = (1-\lambda)Ap_2+\lambda Ap_3$, therefore $$p_2'-p_1' = Ap_2-((1-\lambda)Ap_2+\lambda Ap_3) = \lambda(Ap_2-Ap_3)=\lambda(p_2'-p_3').$$ If $\det A\ne0$, then $p_2\ne p_3$ implies $p_2'\ne p_3'$ and the result follows immediately.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.